Voltage-driven autonomous cooperative control of EHLs for load stabilization - Bing Qi; Rui Liu; Deying Zhang; Zhuoqun Wang; Qi Qi (International Journal of Electrical Power & Energy Systems)
Electric heating loads (EHLs) are considered as effective demand-side resources for supply–demand balance. However, the effective control of EHLs becomes challenging due to their large number and extensive distribution. In this context, this paper proposes a voltage-driven autonomous cooperative control method of EHLs for distribution network load stabilization. Firstly, an optimal control model of EHLs is constructed, where the adaptive historical influence factors are introduced to achieve the dynamic trade-off between load rate stability and user comfort. Then, a voltage-driven distributed control model is developed, which utilizes the mapping relation between node voltages and transformer load rate to minimize the high-frequency communication overhead associated with large-scale EHLs dispatch while ensuring the control timeliness. Finally, a Q-decomposition Multi-agent Independent eXtension (QMIX) algorithm is used to learn the mapping relation, and the EHLs real-time optimal control strategies are generated through the utilization of Centralized Training Decentralized Execution (CTDE) framework. Simulation results demonstrate the effectiveness of the proposed control method of EHLs in stabilizing the transformer load rate and guaranteeing the user comfort, where no control instruction is required during the implementation phase.